NEW ORAL ANTICOAGULANTS IN THE THERAPY OF ANTIPHOSPHOLIPID SYNDROME - M. A. Satybaldyeva; T. M. Reshetnyak (Научно-практическая ревматология)
The vitamin K antagonist warfarin is an essential medicine from a group of anticoagulants, which is used to treat antiphospholipid syndrome (APS). However, it has a number of disadvantages especially in patients who need longterm and frequently lifetime prevention of thromboses. New oral anticoagulants, such as dabigatran etexilate (Pradaxa®), rivaroxaban (Xarelto®), apixaban (Eliquis) and others, have been recently synthesized. Unlike warfarin, they are administered at fixed doses, require neither routine monitoring nor diet, and interact with drugs only in small amounts. The new oral anticoagulants have been approved for certain indications, but the data of performed trials are inapplicable to patients with APS. These medicines are expected to improve quality of life in patients with this condition.